The Development of Venture Capital and Private Equity in GCC Countries - Binhassan, Abdullah (2010)
The rapid economic growth of Gulf Corporation Council (GCC) countries in the last decade, have facilitate the entry of new industries. Private equity industry is no exception, the number of firms and funds grown significantly since 2001. However, the economic recession and the under-developed local corporate governance regulations impacted the flows of international private equity investments, especially, in a region where deal flows and fundraising activities are governed via the local relationships networks, which ultimately resists the investors inflows to the region. Therefore, the study analysis the GCC markets using Wright et al (1992) conceptual framework of private equity development. Doing so will present a well-structured market analysis present the main challenges and drivers of the local market.